EFFECT OF CAPITAL STRUCTURE ON ASSET GROWTH AND FIRM VALUE (STUDY ON SERVICE COMPANIES IN THE PROPERTY AND REAL ESTATE SECTOR ON THE INDONESIA STOCK EXCHANGE) - Mariam Makmur; Fakhruddin Kurnia M; Nur Eva Yanti (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2022)
The Effect of Capital Structure on Asset Growth and Firm Value in Property and Real Estate Sector Service Companies in 2014 on the Indonesia Stock Exchange (IDX). This study aims to examine the effect of capital structure on asset growth and firm value in the property and real estate sectors. The population of this study is the property and real estate sector service companies on the Indonesia Stock Exchange in 2014 totaling 42 companies. The sampling method used is a non-probability sampling approach, namely saturated sample. Data analysis method using Warp –PLS 5.0. The results of the study found that the relationship between capital structure and company value was negative and significant. The relationship between capital structure and firm value mediated by asset growth is negative and significant. This study uses the trade off theory.   Keywords: Capital Structure, Asset Growth and Firm Value.